Surgical site fire during cesarean section - Leena Goel; Greeshma Murdeshwar; Sidhesh Bharne (Wolters Kluwer Medknow Publications, 2013)
Electrocautery has become an indispensable tool in the operating room mainly, to achieve a bloodless surgical field. At the same time, the use of alcohol-based antiseptics, like spirit, is commonly used these days for skin preparation before surgery. However, it does carry several risks including fire burns, with the use of electrocautery in a field smeared with spirit. Here, we report a case of pregnant patient undergoing elective cesarean-section under spinal anesthesia who suffered 17% second degree-superficial partial thickness burns due to electrocautery where spirit was used for skin preparation resulting in circulatory shock managed by inducing general anesthesia. Perioperative management was uncomplicated and both mother and newborn were discharged without any untoward problem. This report highlights general safety issues relating to the risk of fire in all surgical patients and the preventive measures for such injury.